Rancang Bangun Sistem Informasi Rumah Kos Berbasis Web dengan Metode Terapan - Ali Basir; Aries Saifudin (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
In the Jakarta area, there are countless boarding house businesses. For newcomers who are having difficulty finding information about boarding houses, it will be very useful in determining the desired boarding house both from the difference in price, location, available facilities, and room availability. By using technology and information in a business in addition to getting convenience in managing the business that is run and can be used to develop the business that is run so that it will be better and will not be eroded by technological developments today. By using an information system with an easy access method that is run through a website or cellphone for managing boarding houses or viewing rented houses in the Jakarta area. With the PHP programming language and using the Mysql database, it is hoped that it will make it easier for those who want to access this information. So that you no longer have to use the survey method to the desired place or rent.